INTEGRASI MODA TRANSPORTASI TREM DALAM RUANG KOTA (Studi Kasus Ruang Jalan DR. Rajiman dan Jalan KH. Agus Salim Surakarta) - Bondan Prihastomo (Jurnal Tekno Global, 2014)
Surakarta City is one city that has a fairly rapid development in Central Java. The city government had various breakthroughs to organize its spatial quality. Some of the projects the city spatial planning has been conducted among manufacturing citywalk lines on some roads. In addition to the spatial arrangement, the city of Surakarta alsodeveloped a form of public transportation bus called Batik Solo Trans (BST). The issues raised in this paper is the provision of commuter tram transportation within the city of Surakarta. The study was based on a pilot project proposed tram transport provision in the DR Rajiman street and the KH Agus Salim street. Both road corridors that connected each other is supporter of the town's main street corridor Slamet Riyadi street. Slamet Riyadi street that leads to the east takes the path as reversing direction to the west. Provision of trams transport require support in the form of a pedestrian who had direct access to the dismissal. Existing conditions indicate a pedestrian is not yet available in full along the corridor. This becomes an important subject included in the study. This study focuses on the physical setting of the tram line and point of dismissal, with consideration of the needs and activities of the user. Analysis carried out by the comparison between the existing condition to the conditions after the tram line is included to obtain the effectiveness coefficient that can be used as a basis for more detailed planning. The results showed that in general the tram lines can be applied to both corridor with several different changes on each corridor. In each corridor has a different implication for room setting such as site back buildings, wide of roads, vegetation, the presence of street vendors and the current direction of vehicles.